2006
DOI: 10.4018/jcit.2006010103
|View full text |Cite
|
Sign up to set email alerts
|

The Case of Telepsychiatry Adoption and Diffusion in a Healthcare Organization in New Zealand

Abstract: This research investigated telemedicine adoption and usage in psychiatry in one hospital in New Zealand (NZ). This research utilized the technological innovations theories as a guiding theoretical framework to develop a set of determinants of telemedicine adoption in healthcare organizations. The research looked at two stages in the case study concerning the adoption process of telemedicine, utilizing the video conferencing technology (TMVC). Prior to TMVC adoption, the findings suggested that TMVC was adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Thus, telemedicine can be viewed as a process management system that enhances the management, quality, availability, and use of information used in the delivery of healthcare (Atkinson et al , 2001). Telemedicine provides a mechanism for organizations to extend its healthcare‐delivery processes to patients in rural locations, and to areas of low patient volumes for particular services (Al‐Qirim, 2006). The adoption of telemedicine by healthcare organizations is not only changing healthcare‐delivery processes and systems, but also the required skill sets of its personnel.…”
Section: Process Managementmentioning
confidence: 99%
“…Thus, telemedicine can be viewed as a process management system that enhances the management, quality, availability, and use of information used in the delivery of healthcare (Atkinson et al , 2001). Telemedicine provides a mechanism for organizations to extend its healthcare‐delivery processes to patients in rural locations, and to areas of low patient volumes for particular services (Al‐Qirim, 2006). The adoption of telemedicine by healthcare organizations is not only changing healthcare‐delivery processes and systems, but also the required skill sets of its personnel.…”
Section: Process Managementmentioning
confidence: 99%
“…The results revealed that relative advantage, costs, and technical compatibility were the major predictors of adaptation. Al-Qirim (2006) showed that complexity and compatibility were very important factors to the adoption of a video conferencing technology. Kamal (2006) proposed a conceptual IT innovation adoption model that presents a detailed list of factors that impact IT adoption in government sector.…”
Section: Technology-related Factorsmentioning
confidence: 99%